2009
DOI: 10.3181/0807-rm-227
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Iron-Regulatory Genes in Human Hepatocellular Carcinoma and Its Physiological Consequences

Abstract: Hepatocellular carcinoma (HCC) commonly develops in patients with underlying chronic liver disease. Additionally, the tumorous lesions of HCC patients are consistently characterized by the lack of iron accumulation even when arising in iron-loaded liver. However, the molecular mechanism leading to this observed phenomenon is currently poorly understood. In this study, all tumorous tissues from 24 HCC patients with chronic HBV infection were stained negative for iron when histologically assessed by Perls' Pruss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 33 publications
5
45
0
Order By: Relevance
“…patients (6) . The present study showed an increase in the serum levels or positive correlation with CTP or BCLC in transferrin (in CI group), iron (in CI and HCC group) and ferritin saturation (in HCC group), which is in accordance with the literature (11,28,30,38) . A possible explanation is the fact that the iron absorbance through transferrin receptors is higher in hepatocellular carcinoma than in a normal liver, making the transferrin a marker of the presence of HCC (28) .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…patients (6) . The present study showed an increase in the serum levels or positive correlation with CTP or BCLC in transferrin (in CI group), iron (in CI and HCC group) and ferritin saturation (in HCC group), which is in accordance with the literature (11,28,30,38) . A possible explanation is the fact that the iron absorbance through transferrin receptors is higher in hepatocellular carcinoma than in a normal liver, making the transferrin a marker of the presence of HCC (28) .…”
Section: Discussionsupporting
confidence: 80%
“…Some (11,28,30,38) affirm that there are increases in serum transferrin, iron and ferritin saturation levels, positively correlated with the presence of HCV, cirrhosis and HCC, especially in more advanced stages of the diseases. However, other authors have not observed alterations in the iron levels (4) or report reduction in liver cirrhosis and HCC Port GZ, Oliveira K, Soldera J, Tovo CV.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been described that hepcidin mRNA expression is uniformly suppressed in HCC, whereas serum concentration of hepcidin was not correlated with mRNA expression in these studies. [30][31][32] However, up to now the influence of enhanced BMP levels of hepcidin expression in HCC was not analyzed. Remarkably, in spite of enhanced BMP expression in HCC, we were able to detect reduced hepcidin mRNA and protein expression levels in HCC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, two prior studies reported no significant difference in hepcidin or HJV expression, respectively, between HCC and surrounding non-tumorous livers. 31,32 It has to be noted that both studies had been performed with tissue specimens from patients with different ethnic background than in our study. Still, it also has to be considered that some of the mechanisms, which we identified in this study as potential explanation for the missing effect of enhanced BMP levels on hepatic hepcidin expression are already affected in pre-malignant diseased liver tissue, and herewith, may affect iron homeostasis in patients with chronic liver disease.…”
Section: Loss Of Hjv In Hccmentioning
confidence: 92%
“…It has been well documented that iron homeostasis and iron regulatory pathways are abnormal in human HCC (30)(31)(32). Thus, it is likely that iron chelators targeting excess iron may suppress HCC and bring clinical benefits to HCC patients.…”
Section: Discussionmentioning
confidence: 99%